2010
DOI: 10.1158/0008-5472.can-09-2747
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Unfolded Protein Response in Primary Tumors Reveals Microenvironments with Metabolic Variations that Predict Tumor Growth

Abstract: Cancer cells exist in harsh microenvironments that are governed by various factors, including hypoxia and nutrient deprivation. These microenvironmental stressors activate signaling pathways that affect cancer cell survival. While others have previously measured microenvironmental stressors in tumors, it remains difficult to detect the real-time activation of these downstream signaling pathways in primary tumors. In this study, we developed transgenic mice expressing an X-box binding protein 1 (XBP1)-luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 44 publications
(41 reference statements)
4
78
0
Order By: Relevance
“…T-bet and Eomes transcription factors are master regulators of Th1 development and are critical for optimal development of type 1 immune responses (18)(19)(20). In these studies, we evaluated T-bet, Eomes and granzyme B expression within the XBP1-CTL.…”
Section: Memory Cells Within Xbp1-ctl Have Enhanced Expression Of T-bmentioning
confidence: 99%
See 1 more Smart Citation
“…T-bet and Eomes transcription factors are master regulators of Th1 development and are critical for optimal development of type 1 immune responses (18)(19)(20). In these studies, we evaluated T-bet, Eomes and granzyme B expression within the XBP1-CTL.…”
Section: Memory Cells Within Xbp1-ctl Have Enhanced Expression Of T-bmentioning
confidence: 99%
“…16,17 It has been demonstrated that XBP1 is activated in primary mammary tumors, and that its expression correlates with enhanced tumor growth. 18 In support of a direct role for XBP1 in tumorigenesis, the loss of XBP1 was shown to severely inhibit tumor growth. In addition, transformed cells with XBP1 deficiency were sensitized to hypoxia and underwent apoptosis, implicating XBP1 as a survival factor.…”
Section: Introductionmentioning
confidence: 99%
“…The GRP protein family, including GRP78, was originally discovered because of its upregulation in response to glucose deprivation (23). In their in vivo model of microenvironment-driven tumor cell ER stress, Spiotto et al (24) demonstrated that XBP-1-luciferase activity in spontaneous mammary tumors significantly increases when tumor-bearing mice are treated with 2-deoxyglucose (a nonmetabolizable glucose analog) and that glucose deprivation of tumor cells ex vivo causes a dramatic increase in XBP1-luciferase expression. Taken together, these findings demonstrate that hypoxia and low glucose are physiologically relevant inducers of ER stress in tumors in vivo.…”
Section: Glucose Deprivationmentioning
confidence: 99%
“…Hypoxia induced in a HIF-1α-independent manner XBP1 expression and activated splicing of its mRNA, resulting in increased levels of XBP1s (RomeroRamirez et al, 2004). XBP1s colocalizes with hypoxia markers in tumors, and loss of XBP1 increases the sensitivity of transformed cells to hypoxia-induced apoptosis and inhibits tumor growth (Wouters and Koritzinsky, 2008;Spiotto et al, 2010).…”
Section: Hypoxia and The Unfolded Protein Responsementioning
confidence: 99%